2007
DOI: 10.1007/s00270-007-9033-6
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Management of Renal Bleeding after Partial Nephrectomy

Abstract: Angiographic embolization in patients with renal hemorrhage after PN is feasible and has a high success rate. The procedure might facilitate avoidance of nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…However, in cohort studies control of bleeding is reported in 80-100% (Table 6). Our success rates are comparable to other case series [11], but appear to fall within the lower range. Some variance is explained by the generally few cases.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…However, in cohort studies control of bleeding is reported in 80-100% (Table 6). Our success rates are comparable to other case series [11], but appear to fall within the lower range. Some variance is explained by the generally few cases.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, monitoring should be prolonged if any precursor of a complicated course is evident, especially in high-risk cases. Later manifestations of bleeding tend to be symptomatic [11] and were observed up to 3 weeks after NSS in the present study. Further diagnostic measures include contrastenhanced CT of the abdomen and, if an active bleeding site is evident, digital subtraction angiography.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…[ 28,30 -32 ] . Delayed bleeding can be managed angiographically in most cases, but in rare instances nephrectomy may be required [ 28,33 ] . The present haemorrhage incidence of 4% and transfusion incidence of 2% were lower than many published series.…”
Section: Resultsmentioning
confidence: 99%
“…Die TAE findet ferner erfolgreiche Anwendung bei der Beherrschung von renalen Blutungskomplikationen nach offenen oder laparoskopischen Operationen wie der perkutanen Nephrolitholapaxie oder der offenen bzw. laparoskopischen Nierentumorenukleation [2,8,10,12]. Die palliative Embolisation von großen Nierenzellkarzinomen muss in diesem Zusammenhang genannt werden, streng genommen handelt es sich jedoch nicht um ein superselektives Verfahren [7].…”
unclassified